Nurses’ perception of risk factors of phlebitis associated with peripheral intravenous catheter: a cross-sectional study - Daud, Azlina; Mohd Zaki, Noor Isnani (IIUM Press, 2024)
Background: Phlebitis is a main complication of peripheral intravenous catheters. Nurses play an important role in identifying the risk factors of phlebitis in order to reduce the incidence of phlebitis. The purpose of this study is to determine nurses' perceptions of the risk factors for phlebitis. Methods: This cross-sectional study was conducted in Hospital Tengku Ampuan Afzan and a random sample of hospital nurses was recruited. 269 participants were involved in this study. All participants are required to answer the questionnaire which divided into two sections, section A regarding sociodemographic background and section B about perception on the risk factors of phlebitis that consist of ten multiple choice questions. Results: The results showed majority of nurses, 75.8% (204), agreed that phlebitis is a significant problem, while 23.0% (62) thought phlebitis is a moderate problem, and only 1.1% (3) of nurses agreed that phlebitis is a minor problem. Nurses recognized some risk factors for phlebitis; however, more than half of the nurses were unaware that cannula material, size of the cannula, and the characteristics of fluid and drug can affect the development of phlebitis. Conclusion: The study showed that nurses did not fully perceive the risk factors of phlebitis. However, they were knowledgeable about certain risk factors such as the duration for cannula replacement and the insertion site of the cannula. These findings indicate ongoing training for nurses in peripheral intravenous catheter (PIVC) management and education about the risk factors of phlebitis are necessary.